UJI BAKTERIOLOGIS JAHE GILING (Zingiber officinale Rosc.) YANG DIJUAL DI PASAR RAYA KOTA PADANG - Wulandari, Fitri; Periadnadi, Periadnadi; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ One type of spice that is widely used by housewives or society is made of minced ginger (Zingiber officinale Rosc.). Minced ginger sold in Pasar Raya Padang can not be considered clean and hygienic. This is evident from peeling ginger is not perfect, use the same water over and over again for the next wash ginger, there are also traders who do not wash beforehand ginger and minced ginger stalls adjacent to the chicken traders. Contamination by bacteria in the food can still occur, most potential contamination is suspected bacterium Escherichia coli. The study was descriptive, with no way of seeing whether or not the bacteria Escherichia coli and coliform in the samples milled ginger. The method used to determine the bacteriological quality of minced ginger is the MPN method consists of three stages the estimation test, test and test assertion perfection. This research was conducted in the Laboratory of Microbiology Department of Biology, State University of Andalas Padang. From the test results on the prediction turns out almost all positive samples as well as the confirmation test and the test of perfection, to obtain MPN Index 0-240 cells / ml. It is proved that ginger rollers are sold in Pasar Raya Padang poor quality and not qualified to be consumed.Â Â